Recruiting and Retaining the Genius Generation for Virtual Teams from a Generation Z Perspective - McGraw, Laquita; Stewart, Carol (International Journal of Business Research & Information Technology (IJBRIT), 2020)
The concept of a virtual team is expanding as its application is growing with multiple generations in the workforce. A virtual team is now a significant issue in the 21st century because there are currently five generations in the workforce. To lead a multigenerational virtual team, employers must understand a new generation that is entering the workplace. Although Generation Z will bring new characteristic to the workforce, leadership styles must transform to accommodate a newer generation's expectations. This study explores leadership styles to support virtual teams and a new generation. There exist only a few qualitative studies on virtual teams in today's domestic workforce. The researchers wish to gain knowledge of which leadership style works for a virtual team from the perspectives of Generation Z.
Keywords: GENERATION Z; GENIUS; Generation Y; Generation Z; LEADERSHIP; TEAMS; VIRTUAL communities; VIRTUAL work teams; Virtual team; dept.mgt; leadership; peer-reviewed